2022
DOI: 10.1186/s12913-022-07921-7
|View full text |Cite
|
Sign up to set email alerts
|

Access to primary and secondary health care services for people living with diabetes and lower-limb amputation during the COVID-19 pandemic in Lebanon: a qualitative study

Abstract: Background People living with chronic conditions and physical disabilities face many challenges accessing healthcare services. In Lebanon, in 2020, the COVID-19 pandemic and concomitant economic crisis further exacerbated the living conditions of this segment of the population. This study explored the barriers to accessing healthcare services among people living with diabetes and lower-limb amputation during the pandemic. Methods We conducted semi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…46 This incompatible result in this study can be due to the increase in the prices of medicines and the lack of access to new treatments in Lebanon during the pandemic. 47,48 The odds of having difficulties finding psychotropic drugs before the pandemic were higher per increase of 1 year in age. Non-adherence to medication was reported to be higher with age, 49 which may potentially lead to skipping dosage or excess intake of medicines.…”
Section: Discussionmentioning
confidence: 99%
“…46 This incompatible result in this study can be due to the increase in the prices of medicines and the lack of access to new treatments in Lebanon during the pandemic. 47,48 The odds of having difficulties finding psychotropic drugs before the pandemic were higher per increase of 1 year in age. Non-adherence to medication was reported to be higher with age, 49 which may potentially lead to skipping dosage or excess intake of medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the restrictive measures and the fear caused by the COVID-19 pandemic, 70% of our study participants reported fewer visits to the doctor than usual. Other barriers that may have prevented them from accessing healthcare services include the ongoing economic crisis, lack of transportation, and absence of psychosocial support [ 73 , 74 ]. Additionally, COVID-19 pandemic isolation guidelines may have further exacerbated the proportion of people that do not attend follow up visits.…”
Section: Discussionmentioning
confidence: 99%
“…20,23,25 In this study, socioeconomic status was not significantly associated with PAWP, but this might be due to the way patients were approached and to the fact that a pretty homogeneous sample was recruited (ie, relatively well-educated and with moderate or high socioeconomic backgrounds) compared to other studies which looked at the differences in sociodemographic areas where pharmacies were based 20 and in other cross-sectional studies done among the general population living in Lebanon, education and socioeconomic status played an important role in determining preventive behaviors such as cancer screening, 35 health information seeking, 36 or access to healthcare services. 37 Attitudes Towards DAWP and PAWP…”
Section: Reasons For Dawp and Pawpmentioning
confidence: 99%